Group Delay and Dispersion Properties of a Multifunctional, Tunable Optical Reflector using the Asymmetric Crisscrossed Coupled-Microring Reflector Structure - Gutierrez, Avram J (Archīum Ateneo, 2022)
We derive, for the first time to the best of our knowledge, more general and analytical expressions for the reflected complex electric field, intensity, and phase response of a recently reported multifunctional, tunable cross-coupled microring resonators. This allows us to investigate the effects of the parameter asymmetry between the two ring-to-bus directional couplers on the overall behavior of the device. We focus on its effects on the group delay and dispersion properties of the reflected light. Specifically, we explore numerically their profiles when the values of the two directional couplers are varied. Here, we show that it has interesting characteristics such as (i) group delay reveals the existence and the associated parameter conditions for the “slow light” and “fast light”, and (ii) dispersion becomes flat across a wide band when the couplers' asymmetry is increased. These properties are advantageous in optical fiber-based communication applications.